2018
DOI: 10.1088/1361-6528/aaecc6
|View full text |Cite
|
Sign up to set email alerts
|

Construction of noble-metal-free TiO2 nanobelt/ZnIn2S4 nanosheet heterojunction nanocomposite for highly efficient photocatalytic hydrogen evolution

Abstract: A binary nanocomposite composed of two-dimensional (2D) ultrathin ZnIn 2 S 4 nanosheets and one-dimension (1D) TiO 2 nanobelts was prepared and applied as a noble-metal-free photocatalyst for hydrogen evolution under solar-light irradiation. The TiO 2 nanobelt/ZnIn 2 S 4 nanosheet heterojunction nanocomposites show higher light absorption capacity, larger surface area and higher separation of charge carriers in comparison to pristine TiO 2 and ZnIn 2 S 4 . As a result, the hydrogen production over the TiO 2 /Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Wei et al fabricated the highly active noble metal‐free TiO 2 /ZIS composite photocatalysts formed by ZIS nanosheets uniformly deposited on TiO 2 nanobelts through a simple hydrothermal method. [ 88 ] Compared with the pristine TiO 2 and ZIS, the photocatalyst obtained after the composite of ZIS and TiO 2 has larger surface area, higher light absorption capacity, and higher separation of charge carrier, resulting in enhanced photocatalytic hydrogen evolution performance. Chen et al prepared the helical CdS@ZIS core–shell nanocomposites by in situ covering ZIS nanosheets on the surface of 1D CdS nanorods in the hydrothermal environment.…”
Section: Synthetic Strategies Of Zis Photocatalystsmentioning
confidence: 99%
“…Wei et al fabricated the highly active noble metal‐free TiO 2 /ZIS composite photocatalysts formed by ZIS nanosheets uniformly deposited on TiO 2 nanobelts through a simple hydrothermal method. [ 88 ] Compared with the pristine TiO 2 and ZIS, the photocatalyst obtained after the composite of ZIS and TiO 2 has larger surface area, higher light absorption capacity, and higher separation of charge carrier, resulting in enhanced photocatalytic hydrogen evolution performance. Chen et al prepared the helical CdS@ZIS core–shell nanocomposites by in situ covering ZIS nanosheets on the surface of 1D CdS nanorods in the hydrothermal environment.…”
Section: Synthetic Strategies Of Zis Photocatalystsmentioning
confidence: 99%
“…Functional two-dimensional (2D) layered materials generally have a high specific surface area and increased photon absorption to promote reactant diffusion and a large number of active sites; thus, they have been widely investigated as photocatalysts. [45] ZnIn 2 S 4 has the advantages of high activity, favorable chemical stability, and an appropriate band gap, making it suitable for visible light photocatalytic hydrogen evolution applications. [46,[70][71][72][73] Lei et al reported the single ZnIn 2 S 4 photocatalyst for hydrogen evolution.…”
Section: Znin 2 S 4 /Tiomentioning
confidence: 99%
“…[32][33][34][35] Guided by the scientific route of BMS/TiO 2 , the combination of TMS and TiO 2 , constructing AgGaS 2 /TiO 2 , AgIn 5 S 8 /TiO 2 , AgInS 2 /TiO 2 , AgBiS 2 /TiO 2 , CuInS 2 / TiO 2 , and ZnIn 2 S 4 /TiO 2 heterojunction photocatalysts, have been developed for the application of photocatalytic hydrogen evolution via water splitting. [36][37][38][39][40][41][42][43][44][45] However, the systematical summary of TMS/TiO 2 heterojunction photocatalysts is rarely well-introduced expect Yang et al reviewed the ZnIn 2 S 4 -based photocatalysts for hydrogen evolution. [46] This review not only referred to the ZnIn 2 S 4 /TiO 2 based photocatalysts but provided several effective path for further photoactivity enhancement of ZnIn 2 S 4 /TiO 2 based photocatalysts, like doping, vacancy control, and morphology control, which has guiding significance to improve the photocatalytic hydrogen evolution of TMS/TiO 2 photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, ZnIn 2 S 4 has been combined with other semiconductors to improve photocatalytic properties. Thus, it has been combined with oxides, like in [11][12][13][14][15]; it has also been combined with other sulphides, as in [16][17][18][19], or even nitrides and phosphides [20,21]. Additionally, some reviews on its use, or on the use of similar materials, have appeared [22][23][24][25], and our group has done a recent publication including references to the ZnIn 2 S 4 system [26].…”
Section: Introductionmentioning
confidence: 99%